Proceedings of the 2013 International Conference on Advanced Computer Science and Electronics Information 2013
DOI: 10.2991/icacsei.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm of Selecting more than Four Satellites from GNSS

Abstract: -By analyzing the relationship between the GDOP value and the area of the polygon formed with the endpoints of the satellite-receiver unit vectors in 2-D, the optimal satellite-receiver geometry (SRG) and the minimum GDOP value of n satellites( 4 n  ) in 3-D were deduced in this paper. Based on the minimum GDOP value and the optimal SRG in 3-D, a satellite selection algorithm is proposed to solve the problem of selecting more than 4 satellites from GNSS (Global Navigation Satellite Systems). The good performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In this section a brief background on general satellite selection methods shall be given now. As previous studies have shown ([7], [8]) the best possible satellite geometry in terms of achieved DOP (Dilution of Precision) is defined by a number of satellites with the highest possible elevation and all other satellites equally spaced (in azimuth direction) as close to the horizon as possible (Figure 1). This is problematic in that regard that satellites very close to the horizon commonly experience higher multipath as well as more ionospheric and tropospheric disturbances [9].…”
Section: Satellite Selection Heuristic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section a brief background on general satellite selection methods shall be given now. As previous studies have shown ([7], [8]) the best possible satellite geometry in terms of achieved DOP (Dilution of Precision) is defined by a number of satellites with the highest possible elevation and all other satellites equally spaced (in azimuth direction) as close to the horizon as possible (Figure 1). This is problematic in that regard that satellites very close to the horizon commonly experience higher multipath as well as more ionospheric and tropospheric disturbances [9].…”
Section: Satellite Selection Heuristic Backgroundmentioning
confidence: 99%
“…They commonly only work with the geometry itself ( [7], [8], [10]- [13]) and therefore assume all ranging signals to be equally precise, which is usually not the case. Furthermore, the way many methods work makes it hard to introduce any kind of weighting in the selection process.…”
Section: Satellite Selection Heuristic Backgroundmentioning
confidence: 99%
“…The common goal is in general to find a subset of all satellites currently in view which provides the best (whereby best depends on the application) navigation performance under given side conditions. Simple and computationally efficient approaches using only satellite elevation and azimuth were presented by Zhang, Song, and Park . Also, the widespread approach of selecting the highest satellites, assuming the best signal quality with highest elevation, falls into this category.…”
Section: Introductionmentioning
confidence: 99%
“…The common goal is in general to find a subset of all satellites currently in view which provides the best (whereby best depends on the application) navigation performance under given side conditions. Simple and computationally efficient approaches using only satellite elevation and azimuth were presented by Zhang [1], Song [2] and Park [3]. Also the widespread approach of selecting the highest satellites, assuming the best signal quality with highest elevation, falls into this category.…”
Section: Introductionmentioning
confidence: 99%